Advanced engineering mathematics - Jain, R. K. (Alpha Science International, 2007)
Based on the authors' three decades of teaching experience, Advanced Engineering Mathematics presents the fundamentals and theoretical concepts of the subject in an intelligible and easy-to-understand style. The carefully planned chapters make this book an effective tool for teaching the application of mathematics to engineering and scientific problems. The book provides graded sets of examples and exercises that help students understand the concepts and an Answers and Hints section for difficult problems. The exercises emphasize theoretical concepts and provide the practice students need to gain the confidence to apply them. Advanced Engineering Mathematics offers a logical and lucid presentation of both theory and problem solving techniques that ensures students will not ett lost in unnecessary details.